Communication Patterns of Primary Care Physicians in the United States and The Netherlands - Bensing, Jozien M (Blackwell Science Inc, 2003)
BACKGROUND: While international comparisons of medical practice have noted differences in length of visit, few studies have addressed the dynamics of visit exchange. OBJECTIVES: To compare the communication of Dutch and U.S. hypertensive patients and their physicians in routine medical visits. DESIGN: Secondary analysis of visit audio/video tapes contrasting a Dutch sample of 102 visits with 27 general practitioners and a U.S. sample of 98 visits with 52 primary care physicians. MEASUREMENTS: The Roter Interaction Analysis System applied to visit audiotapes. Total visit length and duration of the physical exam were measured directly. MAIN RESULTS: U.S. visits were 6 minutes longer than comparable Dutch visits (15.4 vs 9.5 min, respectively), but the proportion of visits devoted to the physical examination was the same (24%). American doctors asked more questions and provided more information of both a biomedical and psychosocial nature, but were less patient-centered in their visit communication than were Dutch physicians. Cluster analysis revealed similar proportions of exam-centered (with especially long physical exam segments) and biopsychosocial visits in the 2 countries; however, 48% of the U.S. visits were biomedically intensive, while only 18% of the Dutch visits were of this type. Fifty percent of the Dutch visits were socioemotional, while this was true for only 10% of the U.S. visits. CONCLUSIONS: U.S. and Dutch primary care visits showed substantial differences in communication patterns and visit length. These differences may reflect country distinctions in medical training and philosophy, health care system characteristics, and cultural values and expectations relevant to the delivery and receipt of medical services.